2002
DOI: 10.2320/matertrans.43.2832
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Photoluminescence Decay of Porous Silicon Prepared by Rapid Thermal Oxidation and Quenching in Liquid Nitrogen

Abstract: Rapid thermal oxidation and quenching in liquid nitrogen (RTOQN) has been examined on anodized porous silicon (PS). The as-anodized PS samples exhibit a photoluminescence peak at 750 nm that decays instantaneously upon discontinuance of 325-nm He-Cd laser irradiation. In contrast, PS samples after RTOQN show a luminescence peak at 560 nm that decays very slowly (>1 s). In this paper some detailed RTOQN conditions leading to such a slow-decay photoluminescence are defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…A similar emission band has been observed previously by a few other research groups (Kux et al 1995;Kovalenko et al 1999;Wadayama et al 2002). An emission band peaked at about 540 nm was observed for similar excitation wavelengths (337 and 325 nm) (Kovalenko et al 1999;Wadayama et al 2002).…”
Section: Long-lived Bandsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar emission band has been observed previously by a few other research groups (Kux et al 1995;Kovalenko et al 1999;Wadayama et al 2002). An emission band peaked at about 540 nm was observed for similar excitation wavelengths (337 and 325 nm) (Kovalenko et al 1999;Wadayama et al 2002).…”
Section: Long-lived Bandsupporting
confidence: 88%
“…Kovalenko et al (1999) reported a decay time of 0.5 s at 15 K, shorter than that observed by Gelloz andKoshida (2009, 2012), in as prepared but likely slightly aged, as well as in oxidized PSi. Wadayama et al (2002) reported an emission band decaying very slowly (>1 s) at room temperature in PSi having been subjected to rapid thermal oxidation at 1000°C and subsequent rapid cooling in liquid nitrogen. Wadayama et al (2002) reported an emission band decaying very slowly (>1 s) at room temperature in PSi having been subjected to rapid thermal oxidation at 1000°C and subsequent rapid cooling in liquid nitrogen.…”
Section: Long-lived Bandmentioning
confidence: 99%
“…Also, PL properties of PS are strongly influenced by anodization conditions as well as post-treatments. 6,16,17) Most of the PL features thus far reported were concerned with samples exposed to air afterwards; alterations of the surface chemical structure by atmospheric oxygen, water vapor, etc. were unavoidable, which could influence and further complicate the PL behavior of PS.…”
Section: Introductionmentioning
confidence: 99%